A preliminary evaluation of chloro-nicotinyl aphicides as planting-hole treatments against the tobacco aphid Myzus persicae nicotianae - Matanhire, Rutendo (Midlands State University, 2014)
A field trial was done to examine the efficacy of chloro-nicotinyl aphicides applied as soil applications, and to determine the optimum rate for fipronil, acetamiprid and calypso for control of the tobacco aphid Myzus persicae. The tobacco variety KRK26 was used in this experiment. The plants were initially exposed to natural infestation by the tobacco aphid. At eight weeks after planting (WAP) the plants were artificially infested with cultured aphids after an assessment of natural infestation was done. Assessments were done at weekly intervals up to 11WAP. The aphicides thiamethaxom, imidacloprid 350 SC and fipronil at a rate of 500 ml.Ha-1 exhibited efficacies against the aphids comparable to the two standard aphicides actara and confidor. The aphicide thiamethaxom had the highest residual activity as it was able to effectively control aphids even up to the last assessment week (11 WAP), followed by fipronil and then imidacloprid. This indicates that these three aphicides could potentially be used as soil applications to effectively control M. persicae. In contrast, the rest of the treatments showed little or no efficacy against the tobacco aphid. The suitable application rates for the efficacious chemicals were125 ml.100-1 for thiamethaxom, 170 ml.100L-1 for imidacloprid 350 SC and 500 ml.Ha-1 for fipronil.